Outcomes of Surgical Resection versus Medical Management in Chronic Pulmonary Aspergillosis: A Systematic Review and Meta-Analysis of Comparative Cohorts - Avino Mulana Fikri; Fauzar; Roza Kurniati (HM Publisher, 2026)
Background: Chronic pulmonary aspergillosis (CPA) is a progressive and debilitating fungal infection that complicates structural lung diseases, particularly in patients with a history of treated tuberculosis. The therapeutic strategy remains a subject of intense debate, polarized between surgical resection, which offers a potential definitive cure but carries significant operative risks, and long-term azole therapy, which is suppressive but prone to drug resistance and high relapse rates. This study aimed to systematically evaluate survival outcomes and recurrence risks between these two modalities, specifically addressing the clinical heterogeneity between simple aspergilloma (SA) and chronic cavitary pulmonary aspergillosis (CCPA). Methods: We conducted a systematic review and meta-analysis of six pivotal retrospective cohort studies published between 2013 and 2022, representing the modern era of thoracic surgery. Databases including PubMed, Scopus, and Embase were searched for comparative studies reporting overall survival (OS) and recurrence rates. Data were pooled using a random-effects model to account for clinical heterogeneity. The risk of bias was assessed using the Newcastle-Ottawa Scale (NOS), with specific adjustments for allocation bias and confounding factors. Results: The meta-analysis integrated data from 268 patients. Surgical resection was associated with a significant reduction in all-cause mortality compared to medical therapy (Pooled Hazard Ratio [HR] 0.12; 95% CI 0.04–0.35). In stratified analysis, recurrence rates were 2.7% for simple aspergilloma versus 10.3% for CCPA in surgical arms, contrasting sharply with relapse rates of 36–50% in medical arms upon drug cessation. An analysis of adjuvant antifungal therapy in a subset of patients showed no statistical benefit in completely resected simple aspergilloma. Postoperative complications occurred in 24.5% of surgical cases, primarily consisting of prolonged air leaks. Conclusion: Surgical resection offers superior recurrence-free survival in selected candidates with localized disease compared to medical therapy. While effectively curative for simple aspergilloma, surgery in CCPA acts as a cytoreductive measure with a persisting recurrence risk, necessitating a multimodal approach. Medical therapy remains the mainstay for patients with bilateral disease or poor pulmonary reserve, but requires indefinite duration to prevent relapse.